PENERAPAN STRATEGI PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 017 SOREK SATU KECAMATAN PANGKALAN KURAS - Hasmi Hasmi; Zariul Antosa; Munjiatun Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problems underlying this study is the lack of students ability in under standing science. This is caused because in teacing learning process the teachers still use the method of teacher contered. So the students only get the knowledge from the teacher, they aren’t active and lazy to think, ask and comment. The students seldom given opprtunity to discover and develop their ability in building knowledge and learning experience. To overcome the problem above, by implementing the inkuiri learning strategy can develop the students’ ability in learning science of the fifth grade students of SD Negeri 017 Sorek Satu, Pangkalan Kuras District.The subjects of this research were the fifth grade students of SD Negeri 017 Sorek Satu, Pangkalan Kuras District in academic year 2013/2014 by number 27 students. This research design using classroom action research (PTK) done in two cycles. And each cycle is done twice meetings with a repeat meeting with one end of cycle.Which aims to improve the student’s ability of science of the fifth grade students of SD Negeri 017 Sorek Satu, Pangkalan Kuras District for material of Energy. This research shows that the implementing of inkuiri learning strategy can develope student’s ability of science of the fifth grade student’s of SD Negeri 017 Sorek Satu, Pangkalan Kuras District. At the beginning of data base score is 65,86 and for the repetition of cycle I, the student’s score increase become 79 and the student’s score 82 for repetition of cycle II. Based on the explanation above can concluded that the implementing of inkuiri learning strategy can develop the student’s ability of science of the fifth grade student’s of SD Negeri 017 Sorek Satu, Pangkalan kuras District.Keywords : Inkuiri Learning Strategy, Learning Achievement IPA